Qualitative Research and Applications in Colorectal Surgery - Vitous, C. Ann; Suwanabol, Pasithorn A. (Clinics in Colon and Rectal Surgery, 2023)
Traditionally employed in medical anthropologic and sociologic literature, qualitative methods are emerging as an essential component of clinical research as surgeons and researchers strive to optimize care informed by patient perspectives. Qualitative methods in health care–related research may be used to understand subjective experiences, beliefs, and concepts that are not captured using quantitative analyses and to gain in-depth knowledge of a specific context or culture. A qualitative approach may also be employed to explore under-researched problems and generate new ideas. Here, we provide an overview of aspects to consider when designing and conducting a qualitative research study.
Keywords: qualitative research; mixed methods; patient experience